Influence of cryogenic machining by using liquid nitrogen on end milling of CFRTP - Tasuku HIGAINO; Tojiro AOYAMA; Hitoshi OGAWA (Nihon Kikai Gakkai ronbunshu, 2015)
CFRP (Carbon Fiber Reinforced Plastic) is widely used for airplane, automobile and general machinery because of its high specific strength. CFRTP (Carbon Fiber Reinforced Thermo-Plastic) is especially attracting the attention of the viewpoint of recycling and molding speed. In machining of CFRTP, softening of matrix resin causes burrs due to high cutting temperature. In this study, side milling tests are carried out by changing cooling condition (Dry/Cryogenic). Liquid nitrogen (LN2) is used as coolant for cryogenic machining. Cutting temperature, cutting force, surface integrity and tool wear are examined. The cutting temperature of dry condition and cryogenic condition shows 51.2°C and -172.9°C, respectively. The cutting temperature of dry condition is higher than the glass transition point of matrix resin (PA66). It is thought that softening of matrix resin occurs under dry condition. The employment of cryogenic milling effectively suppresses burrs. It is also pointed out that the tool wear is larger than that in dry milling. It is thought that the elastic module of matrix resin influence the occurrence of burrs. In order to examine elastic module of matrix resin (PA66) by changing cooling condition (Room temperature/LN2), the indentation test are carried out on machining center. The elastic module of matrix resin in cryogenic condition is higher than that in room temperature. It is shown that the occurrence of burrs is related to elastic module.